Euphorbia serpens extracts mediated synthesis of copper oxide nanoparticles and their biological applications - Sana Idrees; Banzeer Ahsan Abbasi; Javed Iqbal; Mohsin Kazi (Heliyon)
With the passage of time there is enormous development in the field of science and technology, however, human health remained the utmost concern. There are different strategies that helps us to treat various diseases but they have adverse reactions on our bodies. Nanobiotechnology is the advanced field consisting of new techniques and fabrication procedures for nanostructures for making drugs more effective against diseases in less time. These bio-nanoparticles easily target diseased cells, bind to them and damage the diseased tissue. Green synthesis of CuONPs is multi-purposed and can also be used for several bio-applications. The present study involves fabrication of economically viable copper oxide nanoparticles using aqueous plant extracts. The medicinal plants used in current study were Euphorbia serpens. The orchestrated nanoparticles were validated using several analytical techniques; Ultraviolet–Visible spectroscopy, XRD, SEM, FT-IR (Fourier‐transform infrared), EDS, FT-IR and DLS (Dynamic light scattering). The average/mean size of the greenly fabricated nanoparticles was found to be 20.39 nm. Further, the biosynthesized NPs were evaluated for multiple biological activities. The bactericidal properties of green synthesized NPs were demonstrated using different bacterial strains revealing significant antibacterial potentials. The fungicidal properties were also demonstrated using different fungal strains showing significant antifungal potential. The minimum inhibitory concentration (MICs) values were calculated for different bacterial and fungal strains via disc-diffusion method. Further, our Euphorbia serpens orchestrated nanoparticles revealed excellent cytotoxic potentials against nascent brine shrimp larvae (IC50: 32.88 μg/mL) and have shown potential antioxidant properties. In conclusion, the asynthesized nanoparticles have shown significant in vitro bio-potentials. In future, different in vitro activities; antileishmanial, anticancer, enzyme degradation assays and different in vivo studies using animal models are recommended to further investigate the role of these NPs in different biomedical applications. Also, the formulations of multi-organic functional groups and biometallic NPs with regulated/balanced surface chemistry is worthy for the consideration.